(untitled) (Research, Society and Development, 2023)
Introduction: Post-COVID-19 syndrome is the term applied to various symptoms, some cognitive, persistent, of COVID-19, even after the end of the acute phase of the infection. Objective: to present the cognitive effects of the post-COVID-19 syndrome through collected data and to analyze the relationship between SARS-CoV-2 infection and the development of these clinical manifestations. Methodology: a systematic literature review was performed, based on the search for clinical trials in PubMED and Scielo. Six studies were selected for review. Results: Overall, studies on the cognitive effects of post-COVID-19 syndrome were small and were based on tests and self-assessments, but show that mental confusion, memory loss and difficulty concentrating are the main complaints reported by patients. Discussion: Evidence points out that the cognitive effects of post-COVID-19 syndrome may be related to the severity of COVID-19 infection and previous neurological diseases. The relationship between viral diseases and cognitive effects is already well established, which makes it possible to think that COVID-19 is also capable of affecting the nervous system. The health system must prepare itself to face a great demand related to cognitive sequelae, being necessary to carry out reforms in its structure. Conclusion: the continuation of studies on the post-COVID-19 syndrome is essential for the understanding of a condition that is related to so many cognitive effects.